(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2025)
Peroxisome proliferator-activated receptors (PPARs) are ligand-activated transcription factors that play a crucial role in several physiological processes, including the metabolism of carbohydrates, proteins, and lipids, as well as regulating cellular differentiation, development, and tumorigenesis. Recent research has increasingly focused on the role of PPARs in maintaining physiological homeostasis and their potential as therapeutic targets. These receptors regulate gene expression involved in lipid and glucose metabolism, inflammation, and cellular differentiation. This narrative review aims to assess the current understanding of the health benefits of PPARs, their mechanisms of action, clinical applications, and challenges. The review includes findings from various clinical and experimental studies, along with insights from previous reviews. An exhaustive bibliographic survey was conducted which utilized search engines, such as Pubmed, Scopus, Web of Science, Science direct, Medline, Google Scholar, and ResearchGate. The search strategy involved the use of some key terms including, PPAR, nuclear receptors, transcriptional regulation, PPAR-dependent suppression. PPARs have been shown to exert significant pharmacological effects, especially in the treatment of metabolic disorders, such as diabetes and obesity. They have the ability to modulate cell differentiation, development and inflammation. While there are challenges in optimizing their efficiency, clinical trial studies suggest that PPARs will offer a promising glimpse into the future of personalized and targeted therapies. This narrative review highlights the benefits of PPARs in managing metabolic disorders, cardiovascular diseases, inflammation and even cancer. Further clinical studies are necessary to understand the adverse effects of these receptors and how they can be optimized to maintain their efficiency.